The Graveyard and the Table : The Catholic-Orthodox Borderland in Poland and Belarus. - Shannon, Alex. (Polish Studies - Transdisciplinary Perspectives Series, 2021)
The ethnographic research into death rituals and food practices in the Polish-Belarusian borderland shows that the symbolic boundaries between the Catholic and Orthodox believers are dynamic and situational. The religious identity of the residents is shaped by social relations and norms more than by the institutional frames of both churches.